Investigating the Corrosion Characteristics of Carbon Steel and the Efficacy of Phenolic-Epoxy Coatings in Enclosed Environments - Alsaleh, Saleh Ahmed S (Curtin University, 2023)
This study to evaluate the corrosion behaviour and mechanism when simulating the corrosion effect of carbon steel in closed environments (i.e., CUI conditions or ballast tanks). The samples were immersed in 3.5 wt. %NaCl solution vs. exposed to condensation conditions. Moreover, to identify under which phenolic-epoxy coatings provide maximum corrosion protection to steel in enclosed environments. In conclusion, the case studies demonstrate that heat treatment of the coated panels improves their coating performance in enclosed environments.